Anak Didik Dalam Perspektif Al Qur’an: Kajian Analisis Qs. At-Tahrim 66/6, Qs As-Syuara 26/214, Qs. At Taubah 9/122 dan Qs. An-Nisa 4/170 - Najiha Azzahra; Riha Datul Aisya; Nina Novita; Fajri Masaid; Wismanto Wismanto; Shafa Fakhlevi (Student Scientific Creativity Journal, 2024)
The Koran has explained how important education is which is very influential in the lives of shaping the character of students to become Muslims with noble morals, especially in the field of developing religious education which is used as a basis for learning both in terms of formal, informal and non-formal institutions which have a very important role in it. The aim of this research is to reveal the important position of students in the view of the Qur'an. The method used in this research is a literature study research method, the data source is analyzed interactively using a literature review based on the latest references. The results of the research in this discussion show that based on the presentation of the verses of the Koran, forms of classification regarding students have been explained and of course they have given meaning to the most important subjects and objects in education, namely students, where they are always prioritized to gain an understanding of learning and formation. character, this cannot be separated from the role of an educator who always directs students to become human beings who are not only intellectual in general knowledge but also intelligent in developing their morals.